THE IMPORTANCE OF WEB APPLICATION BASED ASSESSMENT IN TEACHING FOREIGN LANGUAGES - Malika Xodjimuratova; Umarxo’jayeva Hilola Sirojiddinovna (Journals Park Publishing, 2022)
The article describes the importance of Web applications based assessments in English classes. It deals with some problems in the process of teaching and assessing. Moreover, article includes the role of Web applications in enhancing students’ motivation. Nowadays, information communication technology (ICT) has become one of the main part of the education that is always emphasized, especially by foreign language pedagogy scholars.The aim of the paper is to analyze different methods of assessment, including diagnostic assessment, and emphasize the benefits of Web applications based assessment in foreign classes. Furthermore, work includes the best examples of Web applications, which is crucial for efficient teaching and assessing.
Keywords: Web application; ICT; motivation